Anisotropic thermal properties and ferroelectric phase transitions in layered CuInP2S6 and CuInP2Se6 crystals. (December 2017) - Liubachko, V.; Shvalya, V.; Oleaga, A.; Salazar, A.; Kohutych, A.; Pogodin, A.; Vysochanskii, Yu. M.
Abstract: Thermal diffusivity and thermal conductivity have been studied for the layered crystals CuInP2 S6, CuInP2 Se6 from 30 K to 350 K, showing a relevant thermal anisotropy. Heat is much more efficiently transferred within the layers than perpendicular to them. The ferrielectric transition in CuInP2 S6 is proven to be clearly first order while the ferroelectric one in CuInP2 Se6 has a weak first order character. The behavior of the thermal conductivity as a function of temperature in the ferroelectric phases shows that heat conduction is phonon driven. Disorder in the paraelectric phases due to hopping motions of Cu ions significantly reduces the thermal conductivity to extremely low values. Highlights: There is a strong thermal anisotropy in diffusivity and conductivity. Heat is much more efficiently transferred within the layers than perpendicular to them. Disorder due to Cu hopping motions is responsible for the low thermal conductivity. The character of the ferroelectric transitions is established.